Butane Intoxication: A Case Report with Brain Images Resembling Wernicke Encephalopathy and a Delayed Sequela of Slow Orthostatic Tremor - Ting-Yi Tseng; Vai-Hong Fong; Kuei-Hong Kuo; Chien-Tai Hong; Tzu-Hsien Lai (Acta Neurologica Taiwanica)
Butane is a colorless and inflammable gas widely available in daily lives, such as liquefied petroleum gas and fuels for cigarette lighters and camping stoves. It could be misused for recreational purposes, which occasionally leads to mortality and morbidity, including symptoms presumably due to hypoxic encephalopathy. A 34-year-old male with a butane abuse history for 6 years presented with fever, change in consciousness, and seizures. Magnetic resonance imaging of the head showed hyperintensity lesions in the bilateral medial thalamus, hypothalamus, infundibular wall, and periaqueductal gray, typical for Wernicke encephalopathy. After conservative treatment, he was discharged with the sequelae of mental impairment and Parkinsonism. Being abstained from butane for about 1 month, he had a new onset of gait disturbance with slow orthostatic tremor in the lower limbs. Butane encephalopathy may present with brain images typical of Wernicke encephalopathy and a clinical course of delayed deterioration, resembling that of hypoxic encephalopathy.